Analisis Perbandingan Algoritma Discrete Cosine Transform (DCT) Dan Run Length Encoding Pada Kompresi File Mp4 - Ananda Mulia (STMIK Budi Darma, 2022)
Technological development is one of the important aspects in the world of technology information. Many algorithms have been developed to compress files, including Discrete Cosine Transform algorithm and Run Length algorithm encoding. This lesson presents a comparative analysis of the two algorithms based on compressed video files in mp4 file format. This research analysis aims to provide knowledge about which algorithm is more effective between the two algorithms so that space faster file storage and delivery times. Among them Discrete Cosine Transform and Run Length Encoding With Some of these algorithms need to be chosen a more appropriate algorithm so it is necessary to compare the compression algorithms. The exponential method is the one that allows to do comparative analysis of the two algorithms. Thus, we can see which algorithm is more effective and faster to compress mp4 video files.